Applications of Decomposed Theory of Planned Behaviour in Making Decision to Adopt a Career in Social Entrepreneurship - Lucia DURAC; Liliana Mihaela MOGA (European Journal of Interdisciplinary Studies)
The primary objective of the research is to identify the determinants that influence the decision-making process of entrepreneurs in pursuing a social enterprise. The study is based on the Decomposed Theory of Planned Behaviour, which is a well-known framework used to forecast intentions, encompassing social entrepreneurial career intentions. However, prior research has predominantly focused on conventional entrepreneurship. The central aim of this research is to explore whether there are any variations in the factors that influence the intention of establishing a social enterprise as a means of conducting one's own business. The current study specifically investigates the degree of correlation between Decomposed Theory of Planned Behaviour predictors and the intentions of pursuing a socially entrepreneurial career. The research compares the determinants that underlie the decision to launch a social enterprise based on a comprehensive sample of 142 Romanian social entrepreneurs and their evaluations of social entrepreneurial career intentions. The findings validate the widespread impact of attitudes and perceived behavioural control (self-efficacy) on social entrepreneurial career intentions, as well as the effects of subjective norms.